Capacity and impedance characteristics of the lithium-ion battery and mechanical properties of the battery pack under coupled temperature-vibration conditions: an experimental approach - Li, Ran; He, Feiyang; Vargas, Oscar Rojas; Khan, Muhammad (Journal of power sources, 2025)
Since electric vehicles are subject to constant vibration and temperature fluctuations during operation, it is critical to understand the impact of these factors on the performance of batteries and battery enclosures. This study investigates the impact of vibration (random frequencies from 8 Hz to 200 Hz) and temperature (ranging from −20 °C to 60 °C in 10 °C increments) on lithium-ion batteries at varying states of charge (SOC, from 0 % to 100 % in 10 % intervals). A 3D-printed plastic enclosure was used for the battery pack to assess its mechanical performance under operational vibration. Analysis of the experimental data reveals that battery internal resistance shows an upward trend, with increases ranging from 0.1 mΩ to 0.5 mΩ under standard conditions and up to 1 mΩ at low temperatures after vibration. Battery capacity exhibited a slight decline after vibration, typically around 0.5 %, across most conditions. Temperature did not significantly impact the SOC response, with similar resistance and capacity trends observed across the temperature spectrum after vibration. For the battery pack, structural integrity was maintained under thermal and vibrational stress, as indicated by minimal changes in natural frequency (within 0.5 Hz). These results confirm the feasibility and potential of using 3D-printed battery enclosures in practical applications. •Li-ion cells and 3D-printed cases were tested under thermo-mechanical loading.•SOC and internal resistance were tested from −20 °C to 60 °C across all SOC levels.•Vibration slightly raised resistance and reduced SOC, especially at low SOC.•PLA failed at 60 °C, while ABS enclosures remained structurally stable.